2b+h = 4.82
b+2h = 3.70
multiply the second equation by 2:
2b + 4h = 7.40
subtract the first equation from it:
3h = 2.58
h = 0.86
The answer is B, and here's why. Set up a table for "there" and "back" and use the distance = rate * time formula, like this:
d r t
there d 450 t
back d 400 1-t
Let me explain this table to you. The distance is d, we don't know what it is, that's what we are actually looking for. We only know that if we go somewhere from point A to point B, then back again to point A, the distance there is the same as the distance back. Hence, the d in both spaces. There he flew 450 mph, back he flew 400 mph. If the total distance was 1 hour, he flew an unknown time there and one hour minus that unknown time back. For example, if he flew for 20 minutes there, one hour minus 20 minutes means that he flew 60 minutes - 20 minutes = 40 minutes back. See? Now, because the distance there = the distance back, we can set the rt in both equal to each other. If d = rt there and d = rt back and the d's are the same, then we can set the rt's equal to each other. 450t = 400(1-t) and
450t = 400 - 400t and 850t = 400. Solve for t to get t = .47058. Now, t is time, not the distance and we are looking for distance. So multiply that t value by the rate (cuz d = r*t) to get that the distance one way is
d = 450(.470580 and d = 211. 76 or, rounded like you need, 212.
The tower is 61.65 meters tall.
<u>SOLUTION:
</u>
Given that, a pole that is 2.5 m tall casts a shadow that is 1.47 m long.
At the same time, a nearby tower casts a shadow that is 36.25 m long.
We have to find height of the tower.
Now, we know that,
Then, (let it be) n meter tall 36.25 long shadow
So, by cross multiplication method,
This can be written as,
Cross multiplications steps: (To find Single Variable)
- Multiply the numerator of the left-hand fraction by the denominator of the right-hand fraction.
- Multiply the numerator of the right-hand fraction by the denominator of the left-hand fraction.
- Set the two products equal to each other.
- Solve for the variable.
If we rewrite it as y=mx+d (which can be taken from here from subtracting ax and c from both sides, then dividing b, resulting in y=(-a/b)(x)-c/b. We can then substitute -a/b for m and -c/b for d), if d=0, then we have m as a constant and as we add a specific number to y (that number being m) every time the x value increases by 1, it therefore forms a straight line. If d is not 0, then we simply add d to every single number - this is still a straight line due to that we still add a specific number to y every time x increases by 1 every single time
Answer:
a. it has reflectional symmetry with 16 line of symmetry